2002
DOI: 10.1021/jp025895b
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulations of CO2 and N2 Adsorption in Silica Zeolites:  The Impact of Pore Size and Shape

Abstract: Adsorption of CO 2 and N 2 , both as single components and as binary mixtures, in three zeolites with identical chemical composition but differing pore structures (silicalite, ITQ-3, and ITQ-7) was studied using atomistic simulations. These three zeolites preferentially adsorb CO 2 over N 2 during both single-component and mixture adsorption. The CO 2 /N 2 selectivities observed in the three siliceous zeolites vary strongly as the adsorbent's crystal structure changes, with the selectivity in ITQ-3 being the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
169
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 35 publications
15
169
3
Order By: Relevance
“…The simulation results show that the zeolite 13X capacity for CO 2 adsorption is not affected by the presence of N 2 . These results are in line with the observations reported by Goj et al (2002) obtained by molecular simulation and by Harlick and Tezel (2003). The observations showed mixture isotherms in which the amount of CO 2 adsorption is almost unchanged from the analogous single component isotherm.…”
Section: Fixed-bed Co 2 Mixture Adsorptionsupporting
confidence: 92%
“…The simulation results show that the zeolite 13X capacity for CO 2 adsorption is not affected by the presence of N 2 . These results are in line with the observations reported by Goj et al (2002) obtained by molecular simulation and by Harlick and Tezel (2003). The observations showed mixture isotherms in which the amount of CO 2 adsorption is almost unchanged from the analogous single component isotherm.…”
Section: Fixed-bed Co 2 Mixture Adsorptionsupporting
confidence: 92%
“…The adsorption and separation of CO 2 from gas streams is an important area of research, and there are many published works, both experimental and computational, on adsorption and diffusion in bulk zeolite structures [28][29][30][31][32][33][34][35][36][37][38][39][40] using a variety of potential models. [41][42][43][44] Surface effects are very important for adsorption and much less work has been carried out on the adsorption and transport of CO 2 at zeolite surfaces, so this is where we chose to focus our work.…”
Section: Co 2 Adsorption In Zeolitesmentioning
confidence: 99%
“…The quadrupole moment of certain gas varies as following: CO 2 > CO > N 2 > H 2 > CH 4 ≈ Ar ≈ Kr [28]. Goj et al [51] have effectively showed that the zeolites ITQ-3 and ITQ-7 adsorb preferentially the CO 2 to detriment of N 2 . This selectivity has been attributed to a strengthening of Coulombic interactions between the CO 2 molecules versus N 2 and the electric field of zeolites, which might be caused by the quadrupole moment of CO 2 (−1.43 × 10 13 cm 2 ) that is three times greater than that of N 2 .…”
Section: Influence Of Adsorbates Characteristics 221 Influence Of Tmentioning
confidence: 99%
“…Nevertheless, according to Calleja et al [10] and Katoh et al [19] the selectivity of zeolites M-ZSM-5 (M = Li + , Na + , K + , Rb + , Cs + ) might be due to fact that all the CO 2 molecules are adsorbed on the cations sites while N 2 might interact with the wall of ZSM-5. It has also been observed that the zeolites 13X, M-ZSM-5 (M = Li + , Na + , K + , Rb + , Cs + ), ZSM-5, KY, 4A, Na-4A, 5A, clinoptilolite and Na-mordenite, adsorb selectively the CO 2 in the presence of N 2 , O 2 , He, CH 4 , H 2 , C 2 H 4 , C 2 H 6 , SF 6 and Ar [16,18,19,[51][52][53][54][55][56].…”
Section: Influence Of Adsorbates Characteristics 221 Influence Of Tmentioning
confidence: 99%